DIAGNOSIS AND CORRECTION OF COMPLICATIONS OF INSUFFICIENCY OF ANTI-REFLUX FUNCTION OF THE PHYSIOLOGICAL CARDIA IN HIATAL HERNIAS - Babii, O.M.; Prolom, N.V.; Shevchenko, B.F.; Halinska А.M.; Poliak, N.V.; Pakholka, O.V. (World of Medicine and Biology, 2022)
To improve the diagnosis and treatment of complications of the insufficiency of the antireflux function of the physiological cardia in hiatal hernias, an examination was performed on 78 patients. All patients underwent X-ray examination with determination of the type of hiatal hernia and endoscopic examination with detection of non-erosive reflux esophagitis – in 9 (11.5 %) patients, erosive reflux esophagitis in 16 (20.8 %), ulcers of the lower third of the esophagus in 3 (3.8 %), peptic stricture of the lower third of the esophagus in 3 (3.8 %), and Barrett’s esophagus in 3 (3.8 %) patients. It is proposed to stage the treatment of complications of insufficiency of the antireflux function of the physiological cardia in hiatal hernias with the use of conservative therapy, hydrostatic balloon dilatation or argon plasma coagulation and prepare the patient for the second stage of treatment – antireflux surgery.